Importance of probiotics in the prevention and treatment of colorectal cancer - Eslami, Majid; Yousefi, Bahman; Kokhaei, Parviz; Hemati, Maral; Nejad, Zahra Rasouli; Arabkari, Vahid; Namdar, Afshin (Journal of cellular physiology, 2019)
Colorectal cancer (CRC) remains one of the most common and deadly cancers. Intestinal gut microflora is important to maintain and contributes to several intestinal functions, including the development of the mucosal immune system, absorption of complex macromolecules, synthesis of amino acids/vitamins and the protection against pathogenic microorganisms. It is well known that the gut microbiota changes or dysbiosis may have an essential impact in the initiation and promotion of chronic inflammatory pathways and also have a profound different genetic and epigenetic alterations leading to dysplasia, clonal expansion, and malignant transformation. Probiotic bacteria has antitumor activity with various mechanisms such as nonspecific physiological and immunological mechanisms. This review evaluates the effects of microbiota and probiotics in clinical trials, in vitro and animal model studies that have explored how probiotic against cancer development and also discusses the possible immunomodulatory mechanisms. Several mechanisms alteration of the intestinal microflora; inactivation of cancerogenic compounds; competition with putrefactive and pathogenic microbiota; improvement of the host's immune response; antiproliferative effects via regulation of apoptosis and cell differentiation; fermentation of undigested food; inhibition of tyrosine kinase; reduces the enteropathogenic complications before and after colon cancer surgery and improve diarrhea and it's have been able to create the integrity of gut mucosal and have stimulatory effects on the systemic immune system and prevent the CRC metastasis. Research in clinical trials encouraging findings that support a role of probiotics in CRC prevention and improve the safety and effectiveness of cancer therapy even though additional clinical research is still necessary. Several mechanisms alteration of the intestinal microflora; inactivation of cancerogenic compounds; competition with putrefactive and pathogenic microbiota; improvement of the host's immune response; antiproliferative effects via regulation of apoptosis and cell differentiation; fermentation of undigested food; inhibition of tyrosine kinase; reduces the enteropathogenic complications before and after colon cancer surgery and improve diarrhea and it's; have been able to create the integrity of gut mucosal and have stimulatory effects on the systemic immune system and prevent the CRC metastasis.